4D Printing Applications in the Development of Smart Cardiovascular Implants - Kabirian, Fatemeh; Mela, Petra; Heying, Ruth (Frontiers in Bioengineering and Biotechnology, 2022)
Although the development of 3D printing technology increased the reproducibility and accuracy of scaffold’s fabrication, 3D printed scaffolds can still be further improved to resemble the native anatomy. 4D printing is an innovative fabrication approach combining 3D printing and smart materials, also known as stimuli-responsive materials. Especially for cardiovascular implants, 4D printing can promisingly create programmable, adaptable prostheses, which facilitates implantation and/or creating the topology of the target tissue post implantation. In this review, the principles of 4D printing with a focus on the applied stimuli are explained and the underlying 3D printing technologies are presented. Then, according to the type of stimulus, recent applications of 4D printing in constructing smart cardiovascular implants and future perspectives are discussed.